Delimitation of Jurisdiction and Powers of the Russian Federation and Its Federal Subjects: The Role of the Federal Subjects - I. N. Kuznetsov (Теоретическая и прикладная юриспруденция)
The article considers the problem of the role of the constituent entities of the Russian Federation in implementing the mechanism for division of jurisdictions and powers between the Russian Federation and its constituent entities. The author provides a general description of this differentiation mechanism and analyzes its evolution. Now, the division of powers takes place mainly through federal laws. However, the adoption of these laws is within the jurisdiction of the Russian Federation and is carried out through a special procedure — the legislative process. Therefore, the author evaluates the role of constituent entities in the division of jurisdictions and powers mechanism through their role in federal legislation. The author identifies the main problems and formulates a few promising proposals aimed at strengthening the role of the subjects of the Russian Federation and increasing the degree of consideration of their regional interests in the division of powers.